The Return of Religion in France - McCaffrey, E. author. aut Link
VI, 286 p.
Keywords: The author examines how social change and philosophical crisis in the 1980s created the conditions for the return of religion to contemporary French intellectual life. It highlights a critical conjuncture in recent French history when religion was revitalized in French secularism as an expression of individual identity.